2005
DOI: 10.1063/1.2150267
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical preparation of a stable accumulation layer on Si: A synchrotron radiation photoelectron spectroscopy study

Abstract: Chronoamperometric conditioning of float zone n-Si(111) in 2M NaOH solution in the potential range negative from open-circuit potential is performed in a combined electrochemistry/ultrahigh-vacuum surface analysis experiment. Synchrotron Radiation Photoelectron Spectroscopy measurements at the U49/2 beamline at Bessy II using the SoLiAs facility show formation of a ultrahigh-vacuum-stable permanent accumulation layer without junction formation. Comparison of the Thomas–Fermi screening potential and the mean in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…The atomic bilayer (BL) height on the (111) surface is 0.314 nm; hence these steps have heights of about 16BL-36BL. In synchrotron radiation photoelectron spectroscopy (SRPES) it was shown that these surfaces are in an accumulation condition where the Fermi level is located only 0.06 eV below the conduction band edge whereas from the bulk doping, this energetic difference amounts to 0.26 eV [29]. In separate Kelvin probe AFM measurements, it has been found that the negative charge associated with the accumulation condition is located at the step edges of the nanostructure [35] as schematically indicated in Fig.…”
Section: Nanostructured Semiconductor Surfacesmentioning
confidence: 97%
See 1 more Smart Citation
“…The atomic bilayer (BL) height on the (111) surface is 0.314 nm; hence these steps have heights of about 16BL-36BL. In synchrotron radiation photoelectron spectroscopy (SRPES) it was shown that these surfaces are in an accumulation condition where the Fermi level is located only 0.06 eV below the conduction band edge whereas from the bulk doping, this energetic difference amounts to 0.26 eV [29]. In separate Kelvin probe AFM measurements, it has been found that the negative charge associated with the accumulation condition is located at the step edges of the nanostructure [35] as schematically indicated in Fig.…”
Section: Nanostructured Semiconductor Surfacesmentioning
confidence: 97%
“…The former is obtained by CVT (chemical vapour transport) growth [27] and the latter is prepared from H-terminated Si(111) in alkaline solutions either chemically or electrochemically [28,29]. Figure 2 shows the basic atomic structure of the group VI transition metal dichalcogenide layered semiconductor MoTe 2 .…”
Section: Nanostructured Semiconductor Surfacesmentioning
confidence: 99%
“…Electrodeposition of Pt from PtCl 2À 6 complexes onto n-Si yielded different sizes for H-terminated (1 1 1) surfaces and for the step bunched Si surface where the major terraces are (1 1 1) oriented and the bunched steps are likely to show (1 1 0) orientation [19,20]. At step bunched surfaces, the Pt NPs had an average width of 30 nm and a height of 3 nm.…”
Section: Deposition Energetics For Photovoltaic and Photoelectrocatalmentioning
confidence: 98%
“…Synchrotron radiation photoelectron spectroscopy (SRPES) performed on this type of surfaces allows one to establish the valence band onset at 1.06 eV. [37] This distance between the valence band and the Fermi level indicates that the preparation at negative potentials in alkaline solution where strong hydrogen evolution occurs results in the n-type doping effect discussed above. This has been derived from the energetic difference Fermi level to valence band onset with respect to the flat band situation at~0.8 eV.…”
Section: Electrodeposition Of Reverse Transcriptases Ontomentioning
confidence: 98%